Constitutions, courts, and history : historical narratives in constitutional adjudication - Uitz, Renáta. (Budapest ; New York : Central European University Press, 2005)
Emphasizes the role history and historical narratives play in constitutional adjudication. Uitz provocatively draws attention to the often-tense relationship between the constitution and historical precedence highlighting the interpretive and normative nature of the law. Her work seeks to understand the conditions under which references to the past, history and traditions are attractive to lawyers, even when they have the potential of perpetuating indeterminacy in constitutional reasoning. Uitz conclusively argues that this constitutional indeterminacy is obscured by 'judicial rhetorical toolkits' of continuity and reconciliation that allow the court's reliance on the past to be unaccounted for. Uitz' rigorous analysis and extensive research makes this work an asset to legal scholars and practitioners alike. The inquiry in this volume hopes to attract observers of constitutional adjudication, may they be reading constitutional jurisprudence from the quarters of constitutional law, constitutional history, political science or history departments.
Constitutional adjudication haunted by indeterminacy -- Historical narratives in constitutional reasoning : intuitions and myths revisited -- An overview of arguments used in constitutional adjudication -- The constitutional text in the light of history -- Behind historical narratives : the promise of continuity -- The fruits of reconciliation : a bittersweet harvest.
Includes bibliographical references.
Print version record.
English.
JSTOR
Keywords: Constitutional law; Constitutional history; Judicial review -- History; Droit constitutionnel; Histoire constitutionnelle; Contrôle juridictionnel des lois -- Histoire; LAW -- Judicial Power; POLITICAL SCIENCE -- Constitutions; Constitutional law; Constitutional history; Judicial review -- History; Constitutional history; Constitutional law; Judicial review; Verfassungsrecht; Geschichte; Constitutional courts, Constitutional history, Constitutional law, Judiciary, Political philosophy; History